Optimalisasi Metode Pembelajaran Bagi Guru untuk Siswa Berkebutuhan Khusus pada Hambatan Pendengaran - Yury Ulandary; Karimi Karimi; Yeni Irma Normawati; Robiasnyah Setiawan; Zakiah Ulfa (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This community service was carried out by the SLB Global School teacher Jalan H. Agus Salim, Alue Berawa Village, Langsa District, Langsa City. The problem faced is that learning methods for students with special needs are not yet optimal. The aim of the research is to optimize the ability of special education teachers to use learning methods for students with special needs. The method used is descriptive with accompanying presentation, discussion and training techniques for participants regarding the importance of learning methods for students with special needs. The results of this research are that teachers can optimize learning methods for students with special needs who are hearing impaired. So that it can foster differentiated, fun and meaningful learning for children with special needs.